The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
1991
DOI: 10.1364/ao.30.003604
|View full text |Cite
|
Sign up to set email alerts
|

Nd:YAG laser machining with multilevel resist kinoforms

Abstract: We demonstrate that resist kinoforms can be used for laser micromachining. A 10-level resist kinoform, manufactured by electron-beam lithography, was shown to have a diffraction efficiency of 68%. Nine diffraction-limited holes were simultaneously drilled in 0.10-mm-thick stainless steel. Marking in a silicon wafer is also demonstrated.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

1995
1995
2018
2018

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(6 citation statements)
references
References 8 publications
0
6
0
Order By: Relevance
“…This problem can be circumvented by the use of a kinoform. A kinoform is a diffractive optical element (a computer-generated micro-optic component that uses diffraction to manipulate light) which diffracts a laser beam into multiple beams at controlled, predetermined positions (Lesem et al, 1969;Ekberg et al, 1991;Larson et al, 1994). It can be used to create multiple, parallel beams with equal intensity in each beam.…”
Section: (31) Lithographic Patterning Of Surfacesmentioning
confidence: 99%
See 1 more Smart Citation
“…This problem can be circumvented by the use of a kinoform. A kinoform is a diffractive optical element (a computer-generated micro-optic component that uses diffraction to manipulate light) which diffracts a laser beam into multiple beams at controlled, predetermined positions (Lesem et al, 1969;Ekberg et al, 1991;Larson et al, 1994). It can be used to create multiple, parallel beams with equal intensity in each beam.…”
Section: (31) Lithographic Patterning Of Surfacesmentioning
confidence: 99%
“…It can be used to create multiple, parallel beams with equal intensity in each beam. With a kinoform, it is possible to "laser-machine" mutliple pits in a surface at once (Ekberg et al, 1991), an example of which is shown in Fig. 7 (top) (Jartoft and Krantz, 1997).…”
Section: (31) Lithographic Patterning Of Surfacesmentioning
confidence: 99%
“…Ekberg et al (Ekberg et al, 1991) applied the HOE on the Nd:YAG laser and successfully drilled an array of holes on a stainless steel sheet. A series of laser steel welding tests using Gaussian and several HOE reconstructed beams has also been reported (Kell et al, 2007;.…”
Section: Beam Reconstruction With Holographic Optical Elements (Hoe)mentioning
confidence: 99%
“…20,21 Methods were developed to calculate a topology for an optical element focusing light into an arbitrary figure in a focal plane. 20,21 Methods were developed to calculate a topology for an optical element focusing light into an arbitrary figure in a focal plane.…”
Section: Photomask Fabrication Of Computer Generated Optical Elemementioning
confidence: 99%